CIVIL SERVICE LAWS, MERIT, POLITICIZATION, AND CORRUPTION: THE PERSPECTIVE OF PUBLIC OFFICIALS FROM FIVE EAST EUROPEAN COUNTRIES. (21st September 2016) - MEYER‐SAHLING, JAN‐HINRIK; MIKKELSEN, KIM SASS
Abstract : Research on bureaucracy and corruption tends to concentrate on cross‐national research taking countries as the unit of analysis. Yet national‐level measures neglect large differences within countries. This article therefore takes the perspective of individual bureaucrats. It studies how public officials' experience with bureaucratic institutions affects corruption within their sphere of work. Based on a survey of central government officials in five post‐communist states, the article examines how public servants' views on civil service laws, the quality of their implementation, merit recruitment, and the politicization of appointments associate with rumours of kickbacks in their place of work. The analysis shows that merit recruitment is associated with less corruption, while politicization is associated with more corruption. In contrast, civil service laws are negatively associated with corruption only if they are properly implemented. The findings complement and qualify country‐level research, approaching more closely the micro‐foundations of the relation between bureaucracy and corruption.